2004
DOI: 10.1557/jmr.2004.0394
|View full text |Cite
|
Sign up to set email alerts
|

Metalorganic chemical vapor deposition of highly oriented thin film composites of V2O5 and V6O13: Suppression of the metal–semiconductor transition in V6O13

Abstract: Thin films of vanadium oxides were grown on fused quartz by metalorganic chemical vapor deposition using vanadyl acetylacetonate as the precursor. Growth at temperatures ⩾560 °C results in composites of strongly (00l)-oriented V2O5 and V6O13. The dominant phase of the film changes from V2O5 to V6O13, and back to V2O5, as the growth temperature is raised from 560 to 570 °C, then to 580 °C, as evidenced by x-ray diffraction and Rutherford backscattering analyses. This reentrant-type growth trend was interpreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 34 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Low-pressure CVD (LPCVD) has also been used to deposit thin lms of VO 2 onto glass substrates. 116,117 This work demonstrated that variations in the characteristics of the phase transition were a function of lm microstructure. The lms were very dense at 475 C and showed a large change in resistance at 66 C, displaying a small temperature hysteresis in the transition.…”
Section: Chemical Vapour Depositionmentioning
confidence: 72%
“…Low-pressure CVD (LPCVD) has also been used to deposit thin lms of VO 2 onto glass substrates. 116,117 This work demonstrated that variations in the characteristics of the phase transition were a function of lm microstructure. The lms were very dense at 475 C and showed a large change in resistance at 66 C, displaying a small temperature hysteresis in the transition.…”
Section: Chemical Vapour Depositionmentioning
confidence: 72%
“…Thin films of the various vanadium oxides have been deposited by various techniques such as evaporative methods, [23,24] sputtering processes, [25][26][27] chemical vapor deposition, [28] atomic layer deposition, [29,30] pulsed laser deposition (PLD), [31,32] and hydrothermal synthesis. [33] In all cases, the formation of a specific phase can be selected in the growth process by adjusting the growth parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Takahshi et al [112] used vanadyl tri(isobutoxide) VO(0-i-Bu) 3 as a single source precursor for depositing V0 2 thin films by dip-coating, as well as MOCVD at low pressure onto glass substrates, which resulted in discontinuous thin films with fine needle-like V0 2 crystals. Lowpressure CVD (LPCVD) has also been used to deposit thin films of V0 2 onto glass substrates [113,114]. This work demonstrated that variations in the characteristics of the phase transition were a function of film microstructure.…”
Section: Chemical Vapour Depositionmentioning
confidence: 97%